Gambaran Kompetensi Kepribadian Guru Pada Era Milenial - Indriawati, Prita; Susilo, Ganjar; Surya Saputra, Dwi; Seli, Seli (CV RIFAINSTITUT, 2023)
The quality of education is determined by various factors, but the most important and very dominant is the quality of a teacher's personality. Personality for the teacher is very important because with a good teacher's personality, students can follow the good teacher's personality so as to create a noble future. Based on the results of observations and interviews, it was obtained that the role of the teacher's personality competencies had been carried out well in building the character of students at SDN 012. This can be seen from the efforts made by the school in implementing teacher personality competencies in fostering character which is carried out in each subject at school, namely by teaching students tolerance, honesty, discipline, love of the motherland, democracy, caring for the environment, responsibility and preparing students to become citizens of a good country and with character. In an effort to develop the character of SDN 012 students' personality competencies, teachers also experience obstacles, both from students, the school environment, the community and families. However, in this way these obstacles can still be overcome